PERAN GURU PAI DALAM MEMBENTUK KARAKTER PESERTA DIDIK DI MADRASAH TSANAWIYAH NEGERI 2 KOTA MOBAGU PROVINSI SULAWESI UTARA - Allie Anthonie; Sultan Syahril; Yuli Habibatul imamah (UNISAN JURNAL, 2024)
Character education is a crucial aspect in education, especially in the school environment. Forming quality character in students is very important to produce a generation that has morality, positive values and good attitudes in their daily lives. In this research, Islamic Religious Education (PAI) teachers play a central role in shaping the character of students. Islamic religious education is a conscious and planned effort to prepare students to know, understand, appreciate and believe in the teachings of the Islamic religion, accompanied by guidance to respect adherents of other religions in relation to inter-religious harmony so that national unity and integrity can be realized. The aim of this research is to determine the role of PAI teachers in shaping the character of students at Madrasah Tsanawiyah Negeri 2 Mobagu City and to determine the supporting and inhibiting factors for PAI teachers in shaping the character of students at Madrasah Tsanawiyah Negeri 2 Mobagu City. This type of research is qualitative descriptive research. This research was carried out at Madrasah Tsanawiyah Negeri 2 Mobagu City. The subjects in the research were 1 school principal and 1 PAI teacher, at Madrasah Tsanawiyah Negeri 2 Mobagu City. The research instruments used were observation sheets and interview guidelines. Data analysis uses data reduction, data presentation and drawing conclusions. The results of the research show that Islamic religious education teachers in forming the character of students at Madrasah Tsanawiyah Negeri 2 Mobagu City have played a quite good role, where Islamic Religious Education (PAI) teachers have played their role like teachers as teachers. Islamic religious education has taught honesty, discipline, courtesy and example. The practical implications of this research are the importance of strengthening the role of Islamic Religious Education (PAI) teachers in character education, improving the qualifications and competencies of Islamic Religious Education (PAI) teachers, as well as encouraging collaboration between Islamic Religious Education (PAI) teachers and schools and parents in efforts to shape the character of quality students.